Analysis of Financial Performance in Cosmetics Industry Companies Listed on the Indonesian Stock Exchange - Fakhira Irwan; A. Ifayani Haanurat; Asri Jaya (CV. AFDIFAL MAJU BERKAH, 2024)
This study aimsto assess the financial performance of cosmetic companies listed on the Indonesia Stock Exchange during the 2017-2022 period using financial ratios with a quantitative method. The data used is secondary data. The sample consists of 5 companies selected using purposive sampling technique based on certain criteria. The results of the study show that the liquidity ratios (Current Ratio and Quick Ratio) are in good condition, while the solvency ratios (Debt To Asset and Debt To Equity), activity ratios (Fixed Asset Turnover and Total Asset Turnover), and profitability ratios (Return On Asset and Return On Equity) are in poor condition. Keywords: Financial Statements, Financial Performance, Financial Ratios.